Appointment process of open-heart surgery in Shahid Rajaei Heart Hospital using a discrete event simulation approach - Bahare Rahmani Manshadi; Bakhtiar Ostadi; Amirhosein Jalali (Tehran University of Medical Sciences, 2021)
Background: The waiting list is a list of selected patients in the surgical queue. If demand exceeds capacity, the waiting list grows rapidly, which may lead to unacceptable waiting for patients, especially those in need of acute medical care. Patients waiting for heart surgery are placed on the waiting list for surgery, and sometimes the waiting time is longer than patients expect. Reducing the waiting time for medical services, including heart surgery, is one of the challenges of the health system. In this regard, the present study was performed by identifying an effective solution to reduce the queue length of patients undergoing cardiac surgery.   Materials and Methods: In this article, the process of scheduling open heart surgery at Shahid Rajaei Hospital was reviewed and improved with a discrete event simulation approach in Arena simulation software. After designing the process, the existing bottlenecks leading to the long waiting time of the patients were identified. The waiting time and the number of patients visited were determined as the objective function and the patient flow was improved by presenting improvement scenarios and selecting the best scenario.   Results: Simulation results on 66 selected patients in 7 months from October 2020 to May 27, 2021 show that Scenario number 10 has the most improvement in performance criteria but is not applicable in practice. Therefore, due to system limitations, Scenario 2 was selected as the best scenario. Implementing Scenario 2 could reduce the waiting time by 40 percent and increase the number of patients visited by 21 percent.   Conclusion: Patient prioritization methods allow patients with higher needs to receive more services than those with lower urgent needs, although they also have longer waiting times for patients with lower urgent needs.